Association Between Environmental Factors and Asthma Using Mendelian Randomization: Increased Effect of Body Mass Index on Adult-Onset Moderate-to-Severe Asthma Subtypes - Ha, Tae-Woong; Jung, Hae-Un; Kim, Dong Jun; Baek, Eun Ju; Lee, Won Jun; Lim, Ji Eun; Kim, Han Kyul; Kang, Ji-One; Oh, Bermseok (Frontiers in Genetics, 2021)
Although asthma is one of the most common chronic diseases throughout all generations, much remains unclear for its etiology mostly due to its heterogeneous characteristics in many aspects. We aimed to investigate the causal effects of various environmental factors on asthma using Mendelian randomization and to study whether the asthma susceptibility to the causal effect of a risk factor is different between asthma subtypes that are classified by the age of onset, asthma severity, and sex. We performed Mendelian randomization analyses (inverse variance weighted, weighted median, and generalized summary-data-based Mendelian randomization) using the UK Biobank data resource to estimate the causal effects of 69 environmental factors on asthma. Additional sensitivity analyses (i.e., MR-Egger regression, Cochran’s Q test, clumping, and reverse Mendelian randomization) were performed to ensure the minimum or no pleiotropy. For confirmation, two-sample setting analyses were replicated using both SNPs-BMI that had been reported by a meta-genome-wide association study in Japanese and European (GIANT) populations and SNPs-BMI by a genome-wide association study only in control individuals of UK Biobank. We have demonstrated that BMI causally affects the development of asthma, and that the adult onset moderate-to-severe asthma subtype is the most susceptible to the causal inference by BMI. And it is likely that the female subtype is more susceptible to BMI than the male subtype among adult asthma cases. Our findings are providing a cautioning evidence to clinicians that obesity is a considerable risk factor to asthma patients, particularly in adult onset moderate-to-severe asthma cases.